Analisis Konsep Self Care Pada Klien Hipertensi - Martiningsih, Martiningsih; Novieastari, Enie; Rustina, Yeni; Nursasi, Astuti Yuni; Hadi, Ella Nurlaella (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Self-care is fundamental in the care of clients with chronic diseases such as hypertension. The purpose of this paper is to clarify the concept of self-care for hypertensive clients. Literature review with search strategies carried out through Scopus, Ebscohost, Embase, Sciencedirect, PubMed and Google Scholar web sources published from 2012 to 2022 which were then analyzed according to Walker & Avant, S. (1995) to clarify the concept of self-care. This concept analysis shows that self-care has definition attributes as a process of physical and psychological actions carried out by individuals to maintain health, reduce risk and manage disease in an effort to maintain health, avoid risk factors that cause disease and efforts to reduce the effects of disease. Case models, Borderline and Contrary cases, antecedents, consequences, and empirical references to explain the concept of self-care. The definition of the concept of self-care identifies a number of comprehensive attributes, namely actions that include ongoing processes that include physical and psychological activities carried out by individuals in disease management. Nurses are actively involved as educators-counselors who can maximize self-care agency of hypertensive clients in the self-care process. Topics related to self-care should be explored further to advance nursing interventions in managing hypertensive clients. Keywords: Risk Factors, Physical and Psychological, Disease Management, Hypertensive Clients, Self Care.  ABSTRAK Perawatan diri merupakan hal mendasar dalam perawatan klien dengan penyakit kronis seperti hipertensi. Tujuan penulisan ini adalah untuk memperjelas konsep perawatan diri klien hipertensi. Literatur review dengan strategi pencarian yang dilakukan melalui websources Scopus, Ebscohost, Embase, Sciencedirect, PubMed dan Google Schoolaryang diterbitkan dari tahun 2012 hingga 2022 yang selanjutnya dilkaukan analisis konsep menurut walker & Avant,S. (1995) untuk memperjelas konsep self care. Analisis konsep ini menunjukkan bahwa perawatan diri memiliki atribut definisi sebagai proses tindakan fisik dan psiklogis yang dilakukan individu untuk menjaga kesehatan, mengurangi risiko dan menajemen penyakit dalam upaya mempertahankan kesehatan, menghindarkan diri dari faktor risiko yang menyebabkan penyakit dan upaya mengurangi efek dari penyakit. Model kasus, kasus Borderline dan Contrary, anteseden, konsekuensi, dan referensi empiris untuk menjelaskan konsep self care. Definisi konsep self-care mengidentifikasi sejumlah atribut yang komprehensif yaitu tindakan yang mencangkup proses berkelanjutan yang meliputi aktivitas fisik dan psikologis yang dilakukan individu dalam manajemen penyakit. Perawat terlibat aktif sebagai edukator-konselor yang dapat memaksimalkan self-care agency klien  hipertensi dalam proses perawatan diri.Topik yang terkait dengan perawatan diri harus dieksplorasi lebih lanjut untuk memajukan intervensi keperawatan dalam mengelola klien hipertensi. Kata Kunci:  Faktor Risiko, Fisik dan Psikologis, Manajemen Penyakit, Klien Hipertensi, Self Care.